Low rates of restenosis in primary lateral carotid artery endarterectomy - A. Mackevičius; V. Mosenko; K. Laurikėnas; A. Šatavičiūtė; T. Baltrūnas; U. Chernyaha-Royko; N. Demkova; L. Bardachenko (Medičnì Perspektivi, 2020)
Carotid artery endarterectomy (CAE) is a treatment of choice for symptomatic and asymptomatic high-grade carotid stenosis, showing great results in reducing stroke morbidity. The optimal technique of the arterial closure is, however, still under discussion, with both patch angioplasty and primary closure having numerous advantages and pitfalls. The definite evidence is still lacking. The aim of this study was to evaluate the results of the modified primary closure technique during CEA. Incidence of restenosis more than 8 months after the surgery was measured. A retrospective observational study to evaluate modified primary internal carotid artery closure was conducted in Republican Vilnius University Hospital from January 1st, 2014 to December 31st, 2018. The patients were enrolled in the trial during their routine follow-up by their surgeon.  During the visit, after an informed consent was signed, a qualified investigator performed carotid duplex ultrasound scan, documenting the restenosis rates. Patients also filled in the comorbidity assessment questionnaire, which included their smoking habits, history of hypertension and their adherence to antihypertensive medication as well as cholesterol levels and statin therapy, additional related comorbidities. Out of 342 patients that underwent CAE with primary closure in the Republican Vilnius university hospital from 2014 to 2018, 42 patients were identified as deceased, therefore a follow-up was impossible. Out of planned 150 (50%) consequently selected patients, 125 gave an informed consent to be enrolled into the study. Out of those 6 pre-occlusions were established during the review of the patient medical data and therefore were excluded from the study. In general, we analyzed the data of 119 patients and 125 CAE with a modified primary suture closure. The mean follow-up time was 35.78 months (SE 0.992; SD 11,046). At the time of a follow up, 3 (2,4%) carotid artery occlusions were identified and promptly evaluated. Restenosis rates varied: 5,6% of patients had low grade (<50%), 5,6% had moderate grade (50-69%) and 1,6% had high grade (70-99%) stenosis. The modified lateral CAE with primary closure technique, used in our hospital’s contemporary practice has shown to be a promising alternative to the classical primary suture, due to reduced restenosis rates. More prospective and randomized studies are needed to evaluate this technique in comparison to other CAE closure techniques.